Answer:
at 6:06
Step-by-step explanation:
since it took 13 to be half full just add an extra 13 minutes. 5:53+ 13 minutes= 6:06
Since p = x² - 7, you can substitute/plug in p for x² - 7
So:
(x² - 7)² - 4x² + 28 = 5
(p)² - 4x² + 28 = 5 You can factor out -4 from (-4x² + 28)
p² - 4(x² - 7) = 5 Plug in p
p² - 4p = 5 Subtract 5
p² - 4p - 5 = 0 Your answer is C
Answer:
(3) y=(x+3)
Step-by-step explanation:
I'm not sure what is the parent function, but in most graphs if you will shift it to the left or right (negative sign or positive sign, respectively), it will be inside a parenthesis and the opposite sign is the real movement.
For a cubic function these will be the movements:
f(x)=(x+/-h)^3+/-k
Only the opposite sign of h will be the real movement, while k's sign will automatically indicate the correct movement.
h= x-axis movement (horizontal, inside of the parenthesis in the equation)
k= y-axis movement (vertical, outside of the parenthesis in the equation)
Hope it helps
Answer:2.75
Step-by-step explanation: